A visita domiciliar como uma das possibilidades de prática psicológica em instituições da assistência social. - Souza, Severino Ramos Lima de (2019)
This doctoral thesis aims to contribute to discussions about psychological practices in the context of social assistance policy, as it is a relatively recent field of activity for psychology professionals and, therefore, still under construction. In this sense, it focuses on the theme of home visiting as one of the possibilities of psychological practice under this policy. The theoretical framework used is based on the perspective of psychosocial approaches for which psychological phenomena are understood as multidimensional production, engendered by the discourses and practices of men among themselves in the midst of social, historical, cultural and economic events. It intends to analyze and understand the way psychology professionals conceive and practice the practice of home visiting in the set of their attributions, in the context of the social assistance policy and the resonances as to the way of acting and understanding psychology. To support the thesis questions raised, a qualitative-exploratory field research was conducted, guided by the theoretical-methodological principles of the cartography method. As methodological resources were used the field diary and conversation wheels. Four psychology professionals working in social assistance equipment from Recife city participated in the research, all with more than ten years of practice in this context. All the material produced during the research was analyzed in accordance with the clues offered by cartography and in the light of the psychosocial approach, in order to make possible the explanation and understanding of a possible map of the processes that produce the way psychologists are acting in the institutions of science. social assistance, focusing on the practice of home visiting. The data produced pointed pathways of analysis for provisional understandings within the scope of the intentions of this thesis, which led us to conceive the home visit, when performed by psychologists, as one of the possibilities of psychological practice in the field of social assistance policy. due to its potentiality, as a device capable of setting in motion creative forces and forms directed to the transforming-action of individuals and collectivities, within the principles and objectives proposed by the social assistance policy.